MO442ACUTE ADVERSE EFFECTS OF LOW POTASSIUM ON HEART AND KIDNEY*. (29th May 2021) - Saritas, Turgay; Chen, Lu; Babler, Anne; Rix, Anne; Reimer, Katharina C; Jansen, Jitske; Su, Xiao-Tong; Kerker, Andrew S; Cuevas, Catherina A; Menzel, Sylvie; Kuppe, Christoph; Boor, Peter; et al.
Abstract: Background and Aims: Chronic hypokalemia causes kidney fibrosis with cystic lesions and arterial hypertension. In contrast, potassium-rich diet lowers blood pressure. The acute effects of hypo- and hyperkalemia on heart and kidney are not well understood. Method: Wild-type mice were fed with low (LK), normal (NK) and high (HK) potassium diet for 4 and 20 days. Kidneys were examined for site of acute injury, inflammation and fibrosis. Blood analysis of electrolytes and kidney parameters were analyzed. Echocardiography and ECG were used to assess heart function. Further, KCNJ10 knockout mice were used to investigate kidney damage in a genetically induced hypokalemia model. Results: Proximal tubule injury as detected by KIM-1 + staining and yH2AX + DNA-damage was observed after 4 and 20 days of LK diet. Injury was associated with strong Ki-67 + proliferation of proximal tubule cells. No injury was detected in mice on NK and HK diet. After 20 days of LK diet, F4/80 + inflammation and aSMA + extracellular matrix accumulation, typical for fibrosis, were observed. LK mice developed polyurie, volume depletion, loss of body weight and high BUN. Lower cardiac output and signs of myocardial stress was seen in echocardiography and ECG. Consistent with WT mice on LK diet, KCNJ10 knockout mice developed same pattern of kidney injury. Nine months after deletion of KCNJ10, cysts were observed in the proximal tubule in outer medzulla. Conclusion: Acute hypokalemia causes kidney injury and myocardial stress. Cystic lesions originate from late proximal tubule. Hypokalemia should be corrected rapidly to stop progression into kidney fibrosis.